2018
DOI: 10.1371/journal.pone.0194829
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin use and long-term rates of sepsis: A population-based cohort study

Abstract: ObjectiveSepsis is the syndrome of life-threatening organ dysfunction resulting from dysregulated host response to infection. Aspirin, an anti-inflammatory agent, may play a role in attenuating the inflammatory response during infection. We evaluated the association between aspirin use and long-term rates of sepsis as well as sepsis outcomes.MethodsWe analyzed data from 30,239 adults ≥45 years old in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort. The primary exposure was aspirin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Activation of relevant inflammatory cells leads to production and release of a large number of endogenous inflammatory substances, including cytokines, lysosomal enzymes, vasoactive substances, plateletactivating factors, bradykinin, and alexin; these inflammatory factors interact to create a cytokine storm that causes systemic organ and tissue damage. 3,4 Increased levels of inflammatory mediators, such as tumor necrosis factor a (TNF-a) and interleukins (e.g., IL-6, IL-1, and IL-10), are closely related to the development of sepsis; higher serum concentrations of IL-6 and IL-10 have been associated with a more serious state of sepsis. [5][6][7] Patients with sepsis often exhibit an oxidative stress state that triggers the release of excess free radicals, thereby causing oxidative damage and aggravating the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of relevant inflammatory cells leads to production and release of a large number of endogenous inflammatory substances, including cytokines, lysosomal enzymes, vasoactive substances, plateletactivating factors, bradykinin, and alexin; these inflammatory factors interact to create a cytokine storm that causes systemic organ and tissue damage. 3,4 Increased levels of inflammatory mediators, such as tumor necrosis factor a (TNF-a) and interleukins (e.g., IL-6, IL-1, and IL-10), are closely related to the development of sepsis; higher serum concentrations of IL-6 and IL-10 have been associated with a more serious state of sepsis. [5][6][7] Patients with sepsis often exhibit an oxidative stress state that triggers the release of excess free radicals, thereby causing oxidative damage and aggravating the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…However, a Canadian population-based case-control study of 449 patients and 4 156 controls receiving hemodialysis reported no association between ASA use and risk of vascular access-related infections and sepsis (OR, 1.03; 95% CI, 0.82–1.28), which remained unchanged with increasing ASA dose [21]. Also in support of our findings, a recent US historical cohort study of 30 239 patients reported an aHRR of 0.99 (95% CI, 0.88–1.12) for hospitalization with sepsis associated with ASA use [22].…”
Section: Discussionsupporting
confidence: 82%
“…The majority of previous studies did not access microbiological data to identify infections, including sepsis [21–23]. Thus, misclassification cannot be entirely ruled out, and some lacked complete follow-up [22, 25]. Moreover, information on ASA exposure use was in some cases collected exclusively from medical charts that may be incomplete [10, 25], and variations in the duration of ASA use were not taken into account [10, 21, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-three percent of individuals reported ASA use and the median follow-up was 6.2 years. No associations between long-term exposure to ASA and onset of sepsis and sepsis-related death were found [ 57 ]. In 2020, the ANTISEPSIS trial was published: 16,703 participants aged 70 years and older without major illnesses were enrolled and followed up for a median of 4.6 years.…”
Section: Resultsmentioning
confidence: 99%